2016
DOI: 10.1007/s11481-016-9701-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation and Prevention of Autoimmune Disease by Repeated Sequences from Parasites Linked to Self Antigens

Abstract: Parasite proteins containing repeats are essential invasion ligands, important for their ability to evade the host immune system and to induce immunosuppression. Here, the intrinsic suppressive potential of repetitive structures within parasite proteins was exploited to induce immunomodulation in order to establish self-tolerance in an animal model of autoimmune neurological disease.We tested the tolerogenic potential of fusion proteins containing repeat sequences of parasites linked to self-antigens. The fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…Beside dominant suppression mediated by Tregs, peripheral tolerance ( 3 ) also involves deletion of antigen-specific cells by activation-induced cell death ( 60 ) and anergy ( 4 ), e.g., failure of antigen-reactive cells to produce pro-inflammatory cytokines. The data of this study point to a partial deletion of antigen-specific effector cells upon injection of pOVA-PEG, as also found upon vaccination with multimerized T cell epitopes ( 61 ) and T cell epitopes linked to parasite-derived tandem repeats ( 17 ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Beside dominant suppression mediated by Tregs, peripheral tolerance ( 3 ) also involves deletion of antigen-specific cells by activation-induced cell death ( 60 ) and anergy ( 4 ), e.g., failure of antigen-reactive cells to produce pro-inflammatory cytokines. The data of this study point to a partial deletion of antigen-specific effector cells upon injection of pOVA-PEG, as also found upon vaccination with multimerized T cell epitopes ( 61 ) and T cell epitopes linked to parasite-derived tandem repeats ( 17 ).…”
Section: Discussionsupporting
confidence: 65%
“…In a preceding study, a tolerogenic effect of peptide epitopes was only observed when the peptide was multimerized or coupled to a repetitive carrier protein, but not as native peptide ( 17 ). This let us hypothesize that just molecular size is an important parameter in the tolerogenic efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this often leads to the production of mainly IgM and limited B cell memory (175). In addition, exposure to antigens containing repeated motifs can result in the suppression of an ongoing T cell response (176, 177). …”
Section: Dysregulation Of B Cellsmentioning
confidence: 99%
“…However, this direction is still worth trying since the clinical efficacy of existing immunotherapy to AE diseases has a distance to the ideal therapeutic expectation. As an example, taking advantage of the trait that repeated sequences from parasite are of essence to evade the host immune system, researchers linked repetitive structures from specific parasite proteins to defined self/T-cell epitopes together, tested and verified successfully the effectiveness to induce antigen-specific tolerance (169). …”
Section: Future Directionsmentioning
confidence: 99%